Sludge conditioning using the composite of a bioflocculant and PAC for enhancement in dewaterability. (October 2017) - Guo, Junyuan; Chen, Cheng
Abstract: This study investigated the production of a bioflocculant by using rice stover and its potential in sludge dewatering. Production of the bioflocculant was positively associated with cell growth and highest value of 2.37 g L −1 was obtained with main backbone of polysaccharides. The bioflocculant showed good performances in sludge dewatering, after conditioned by this bioflocculant, dry solids (DS) and specific resistance to filtration (SRF) of typical wastewater activated sludge reached 19.3% and 4.8 × 10 12 m kg −1, respectively, which were much better than the ones obtained with chemical flocculants. Sludge dewatering was further improved when the bioflocculant and polyaluminum chloride (PAC) were used simultaneously, and the optimized conditioning process by the composite was bioflocculant of 10.5 g kg −1, PAC of 19.4 g kg −1, and pH of 8.1. Under this optimal condition, DS and SRF of the sludge appeared as 24.1% and 3.0 × 10 12 m kg −1, respectively. Highlights: Hydrolyzate from acid treated rice stover were used to produce bioflocculant. Relationship of cell quantity and bioflocculant production was discussed. Characteristics of the bioflocculant were examined. Application of the bioflocculant in sludge dewatering was investigated.